Valoración económica de dos variedades de arroz (Oryza sativa), aplicando un pool de microorganismos eficientes para el control de la chinche de arroz. - Alcívar Lascano, Karla Stefanía (2019)
The present project entitled: Economic valuation of two rice varieties (Oryza sativa), applying a pool of efficient microorganisms for the control of the rice bug, carried out on the “La María” campus of the Quevedo-Mocache State Technical University, Its purpose is to present new alternatives for planting rice cultivation, since they are environmentally friendly microorganisms, helping the farmer reduce his production costs and generate greater profits. Its general objective is to: Economically evaluate the effect of efficient microorganisms on the yield of rice cultivation, as means of control of the bed bug. Ten treatments that resulted from the combination of two rice varieties and five insect controllers were tested. The number of panicles, weight in grams per panicles, sterility of panicles and yield were evaluated, additionally the economic analysis of the performance was made based on the costs of the treatments. From the analysis and interpretation of the results, it was concluded that: the Iniap 16 variety presented the highest number of panicles per square meter, surpassing the F-50 variety with 21 panicles; However, the average weight per panicle was 8.3 g in the F-50 variety, it is also observed that the lowest percentage of panicle sterility was recorded in the Iniap 16 variety with 28.0%. With the application of Metharizium Anisopliae, a lower percentage of panicle sterility was obtained with the Iniap 16 variety. The highest yield and the greatest marginal utility was achieved, which means additional values above what is obtained as a benefit in the control. Keywords: Efficient microorganisms, economic analysis, performance, treatment costs.